1996
DOI: 10.1093/infdis/174.supplement_1.s73
|View full text |Cite
|
Sign up to set email alerts
|

The Development Of Multivalent Bovine Rotavirus (Strain Wc3) Reassortant

Abstract: Laboratory and clinical studies have been directed toward development of a vaccine against rotavirus gastroenteritis in infants. First, bovine rotavirus strain WC3, which did not induce neutralizing antibodies to predominant human rotavirus (HRV) serotypes, was determined to be safe and immunogenic; however, it was not protective in all efficacy trials. HRVs adapted to cell culture retained some virulence for infants, but when further attenuated by cold adaptation, they were poorly immunogenic. Reassortant rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
124
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(126 citation statements)
references
References 20 publications
0
124
0
2
Order By: Relevance
“…In contrast, in clinical trials in which WC3 was protective, an immune correlate of protection was not identified. 70 Moreover, correlations with protection were also not found in early studies with various WC3/HRV reassortants. 70 In at least 3 very large studies with RV5 in different settings the rates of serum RV-NA and protection have been determined simultaneously; in most cases protection against disease has exceeded the seroresponse rate.…”
Section: Rv5 and Its Precursorsmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, in clinical trials in which WC3 was protective, an immune correlate of protection was not identified. 70 Moreover, correlations with protection were also not found in early studies with various WC3/HRV reassortants. 70 In at least 3 very large studies with RV5 in different settings the rates of serum RV-NA and protection have been determined simultaneously; in most cases protection against disease has exceeded the seroresponse rate.…”
Section: Rv5 and Its Precursorsmentioning
confidence: 95%
“…70 Moreover, correlations with protection were also not found in early studies with various WC3/HRV reassortants. 70 In at least 3 very large studies with RV5 in different settings the rates of serum RV-NA and protection have been determined simultaneously; in most cases protection against disease has exceeded the seroresponse rate. 67,[71][72][73] No statistical analysis of serum RV-NA as a CoP in these studies has been presented.…”
Section: Rv5 and Its Precursorsmentioning
confidence: 95%
“…In 1999, however, due to a rare association between vaccine use and severe bowel obstruction in vaccinees, the vaccine was withdrawn from the US market (CDC, 1999a, b). Despite these serious adverse effects of vaccination with RotaShield, further efforts at finding safe and effective vaccines are under way (Clark et al, 1996;Bernstein et al, 1998;Clements-Mann et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This is a vaccine similar to RIT 4237 in that it was derived from a G6 serotype bovine strain (P type 5) that was isolated from a calf with diarrhea in Pennsylvania [21]. The vaccine underwent 12 cell-culture passages prior to evaluation in two efficacy trials.…”
Section: Wc3 (Non-reassortant)mentioning
confidence: 99%
“…RotaTeq (RV5) is a pentavalent vaccine with five separate reassortant viruses, each one that incorporates either a VP7 (G1, G2, G3, G4) or VP4 (P8) gene from a human rotavirus strain on the RNA backbone of the previously discussed WC3 bovine rotavirus strain [21]. Thus, the naturally attenuated WC3 bovine virus was altered to provide crossprotection against epidemiologically important human rotavirus strains.…”
Section: Bovine-human Reassortants (Wc3; Rotateq)mentioning
confidence: 99%